The Role of M Bloc Space as A Creative Space in Forming Popular Culture Among Youth in Jakarta - Latip, Abdul; Putra, Lisa Aditia; Imansari, Nadia (UI Scholars Hub, 2024)
Background: Along with the development of the creative industry, more and more public spaces in the form of creative spaces are found as supporting infrastructure for this creative economic activity. This creative space is then indicated to be one of the factors forming popular culture in urban areas. M Bloc Space, a creative space located in South Jakarta. The space was built through the revitalization process of an old building owned by Perum Peruri into a dynamic creative activity center. Aims: This study aims to analyze the role of M Bloc Space in the formation of popular culture among young people in Jakarta. Methods: This research uses a spatial production theory approach using primary data from field observations and interviews as well as secondary data from literature reviews. Results: This study found that M Bloc Space not only provides facilities for various creative activities, but also creates a space for social interaction. Conclusion: The interaction between the three dimensions of space formation makes the role of M Bloc Space relevant in the formation of popular culture, especially among young people in Jakarta.